Protein kinase A regulates C‐terminally truncated CaV1.2 in Xenopus oocytes: roles of N‐ and C‐termini of the α1C subunit. (23rd March 2017) - Oz, Shimrit; Pankonien, Ines; Belkacemi, Anouar; Flockerzi, Veit; Klussmann, Enno; Haase, Hannelore; Dascal, Nathan
Abstract : Key points: β‐Adrenergic stimulation enhances Ca 2+ entry via L‐type CaV 1.2 channels, causing stronger contraction of cardiac muscle cells. The signalling pathway involves activation of protein kinase A (PKA), but the molecular details of PKA regulation of CaV 1.2 remain controversial despite extensive research. We show that PKA regulation of CaV 1.2 can be reconstituted in Xenopus oocytes when the distal C‐terminus (dCT) of the main subunit, α1C, is truncated. The PKA upregulation of CaV 1.2 does not require key factors previously implicated in this mechanism: the clipped dCT, the A kinase‐anchoring protein 15 (AKAP15), the phosphorylation sites S1700, T1704 and S1928, or the β subunit of CaV 1.2. The gating element within the initial segment of the N‐terminus of the cardiac isoform of α1C is essential for the PKA effect. We propose that the regulation described here is one of two or several mechanisms that jointly mediate the PKA regulation of CaV 1.2 in the heart. Abstract: β‐Adrenergic stimulation enhances Ca 2+ currents via L‐type, voltage‐gated CaV 1.2 channels, strengthening cardiac contraction. The signalling via β‐adrenergic receptors (β‐ARs) involves elevation of cyclic AMP (cAMP) levels and activation of protein kinase A (PKA). However, how PKA affects the channel remains controversial. Recent studies in heterologous systems and genetically engineered mice stress the importance of the post‐translational proteolytic truncation of the distal C‐terminus (dCT) of the main (α1C ) subunit. Here, we successfully reconstituted the cAMP/PKA regulation of the dCT‐truncated CaV 1.2 in Xenopus oocytes, which previously failed with the non‐truncated α1C . cAMP and the purified catalytic subunit of PKA, PKA‐CS, injected into intact oocytes, enhanced CaV 1.2 currents by ∼40% (rabbit α1C ) to ∼130% (mouse α1C ). PKA blockers were used to confirm specificity and the need for dissociation of the PKA holoenzyme. The regulation persisted in the absence of the clipped dCT (as a separate protein), the A kinase‐anchoring protein AKAP15, and the phosphorylation sites S1700 and T1704, previously proposed as essential for the PKA effect. The CaV β2b subunit was not involved, as suggested by extensive mutagenesis. Using deletion/chimeric mutagenesis, we have identified the initial segment of the cardiac long‐N‐terminal isoform of α1C as a previously unrecognized essential element involved in PKA regulation. We propose that the observed regulation, that exclusively involves the α1C subunit, is one of several mechanisms underlying the overall PKA action on CaV 1.2 in the heart. We hypothesize that PKA is acting on CaV 1.2, in part, by affecting a structural 'scaffold' comprising the interacting cytosolic N‐ and C‐termini of α1C . Key points: β‐Adrenergic stimulation enhances Ca 2+ entry via L‐type CaV 1.2 channels, causing stronger contraction of cardiac muscle cells. The signalling pathway involves activation of protein kinase A (PKA), but the molecular details of PKA regulation of CaV 1.2 remain controversial despite extensive research. We show that PKA regulation of CaV 1.2 can be reconstituted in Xenopus oocytes when the distal C‐terminus (dCT) of the main subunit, α1C, is truncated. The PKA upregulation of CaV 1.2 does not require key factors previously implicated in this mechanism: the clipped dCT, the A kinase‐anchoring protein 15 (AKAP15), the phosphorylation sites S1700, T1704 and S1928, or the β subunit of CaV 1.2. The gating element within the initial segment of the N‐terminus of the cardiac isoform of α1C is essential for the PKA effect. We propose that the regulation described here is one of two or several mechanisms that jointly mediate the PKA regulation of CaV 1.2 in the heart.